2009
DOI: 10.1002/ps.1780
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of metsulfuron‐methyl residues in wheat field soil: a comparison of HPLC and bioassay techniques

Abstract: Lentil seed bioassay is a more sensitive technique than HPLC. Traces of residues detected in subsurface soil indicated the mobility of metsulfuron-methyl into lower layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Our study highlighted that the estimated half-life of herbicide by HPLC was lower than that of bioassay ( Paul et al (2009), the half-lives of metsulfuron-methyl by HPLC and bioassay were found to be 6.3-7.8 and 17.5 days, respectively. The ability of a soil residual herbicide to have a phytotoxic effect on a sensitive crop depends on the half-life of the herbicide being used.…”
Section: Comparison Of Sulfosulfuron Persistence In Field Soil By Hplmentioning
confidence: 64%
See 3 more Smart Citations
“…Our study highlighted that the estimated half-life of herbicide by HPLC was lower than that of bioassay ( Paul et al (2009), the half-lives of metsulfuron-methyl by HPLC and bioassay were found to be 6.3-7.8 and 17.5 days, respectively. The ability of a soil residual herbicide to have a phytotoxic effect on a sensitive crop depends on the half-life of the herbicide being used.…”
Section: Comparison Of Sulfosulfuron Persistence In Field Soil By Hplmentioning
confidence: 64%
“…The pots were sub-irrigated as needed during the experiment. The plants were uprooted to measure the sulfosulfuron effects on plants root and shoot length at 15 days after planting (Paul et al, 2009). During the experiment, temperature and relative humidity were fluctuated between 18-25 °C and 58-85%, respectively.…”
Section: Bioassay Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…The toxicity of the degradation products after fungal transformation was tested using a lentil seed bioassay (Paul et al 2009). Pre-germinated seeds of Lens culinaris were sown in plastic well trays containing 500 g of uniformly distributed sterile perlite as the supporting medium.…”
Section: Toxicity Of MM Detoxification Productsmentioning
confidence: 99%